Technology innovation, technology complexity, and co-creation effects on organizational performance: The role of government influence and co-creation - Thang Nam Huynh; Phuong Van Nguyen; Quynh Ngoc Nguyen; Phuong Uyen Dinh (Journal of Open Innovation: Technology, Market and Complexity, 2023)
This study aims to identify key determinants impacting technology innovation and organizational performance, investigating how technological complexity and co-creation can enhance technology innovation and organizational performance. It also examines the role of government influence in stimulating technology innovation. The article extends the technology-organization-environment (TOE) framework to build a research model that supports hypothesis development. A survey design method collected data from 323 members of management teams in the manufacturing industry in Vietnam. A structural equation modeling approach enabled estimating the forecasted multidynamic relationships. The findings indicate that technological complexity, government influence, and co-creation significantly enhance technology innovation. Moreover, technological complexity, technology innovation, and co-creation stimulate organizational performance. Specifically, the results show government influence and organizational performance indirectly affecting organizational performance. The findings provide valuable insights for both academia and practitioners, offering a deeper understanding of the complex dynamics between determinants. A manufacturing industry could effectively utilize this study to implement innovative practices in its specific context.